Avaliação da biodigestão anaeróbia da mistura de resíduos avícolas e lácteos - Parzianello, Jorge Eraldo (2011)
This work developed in the laboratories of chemistry UTFPR, aimed to evaluate the anaerobic digestion of waste from the production of cheese (whey) mixed with wastes from the production of broilers (bed), using different concentrations of this mixture. We evaluated the ability of biogas production, the retention time in the digester, the chemical oxygen demand (COD), Total Nitrogen, phosphorus, pH, total solids, fixed and volatile. The digesters were made from PET bottles. The system used was the continuous flow is not the end of the process was defined by the end of anaerobic digestion. In order to check the amounts of serum and litter that would influence the process of anaerobic conditions was performed 22 complete factorial design with central point in duplicate. Experiments were performed to find the best condition of efficiency of biogas. The readings of the pH values were always lower than the initial values. The acidity-alkalinity ratio at the end of the process of digestion was higher than allowed for a good development microbiology. Factors such as lack of adjustment of pH, presence of leaks and acidity-alkalinity relationship may have contributed to the low efficiency of the anaerobic process.